Mixed Electoral Systems - Ferrara, F. author. aut Link
XII, 184 p.
Keywords: Using election returns, public opinion surveys, and legislative roll-call data from many mixed systems in every world region, the authors show that contamination systematically affects party strategy, voting behaviour, legislative cohesion and overall structure of partisan competition.